2002
DOI: 10.1021/ef020106a
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Recovering of a Zn-Doped Manganese Oxide as a Regenerable Sorbent for Hot Coal Gas Desulfurization

Abstract: The performance of a ZnO-doped manganese oxide MZ(1:0.1) as a regenerable sorbent for hot coal gas desulfurization in 70-cycles tests in a fixed bed reactor has been studied. Sulfidation has been carried out at 700 °C using a simulated RKW coal gas, while regeneration of the sulfided sorbent has been conducted at 800 °C using pure air. The performance was very good as deduced from low pre-breakthrough H2S concentration in the outlet gas, high sorbent efficiency, and long durability. Despite that, a slight effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…Doping with chromium oxide [92] and manganese [93][94][95][96]. Also addition of molybdenum [97], vanadium [96][97][98][99] Doping other metal ions into manganese oxide such as Zn [104][105][106], Fe [106] and Al [107][108][109]. Desulfurization at temperatures higher than 700 • reduces the chances of sulfate formation [96].…”
Section: Cuomentioning
confidence: 99%
“…Doping with chromium oxide [92] and manganese [93][94][95][96]. Also addition of molybdenum [97], vanadium [96][97][98][99] Doping other metal ions into manganese oxide such as Zn [104][105][106], Fe [106] and Al [107][108][109]. Desulfurization at temperatures higher than 700 • reduces the chances of sulfate formation [96].…”
Section: Cuomentioning
confidence: 99%
“…Similarly, Slimane and Hepworth [14,15] also found that manganese-based sorbents presented high initial sorption rate, high sulfur capacity and good regenerative ability during hot coal gas desulfurization at 700-1000 • C but with high H 2 S equilibrium concentration (around 150 ppmv). Therefore, a variety of oxides, such as zinc oxide [16][17][18][19], iron oxides [18,[20][21][22], copper oxides [19,21,23,24], and vanadium oxides [25,26] were incorporated into manganese oxides in order to increase the H 2 S removal efficiency. However, the application of zinc and ferric oxides is limited to a maximum temperature of 600 • C due to zinc evaporation and the reduction of ferric oxides at reductive atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Thehighertheoxidationstateofmanganeseis,themoreeasily S 6+ mightformduringlow鄄temperatureSCRprocess.Somuch moreS 4+ isfoundforMnO x 鄄CeO x /ACF T andmuchmoreS 6+ is foundforM鄄MnO x 鄄CeO x /ACF T (M=Fe,Cu,orV). FT鄄IRspectraofthedeactivatedcatalystsafterthermal treatmentareshowninFig.8.ThespectraofMnO x 鄄CeO x /ACFT exhibitadsorptionpeakscorrespondingtothestretchingvibration ofMn-O [25] (605cm -1 )andC -O(1392cm -1 )whichindicate theoxygenatedgroupsonthesurfaceofthecatalysts.The adsorptionpeakcenteredat837cm -1 isassignedtothestretching vibrationofS-O.M鄄MnO x 鄄CeO x /ACF T (M=Fe,Cu,orV)shows almostthesamespectraofMnO x 鄄CeO x /ACF T .Theadsorption peakcenteredat500cm -1 isassignedtooutplaneblendingvib鄄 rationofSO 2-3 whichindicatessulfitesinthedeactivatedcatalysts afterthermaltreatment.Thecharacteristicadsorptionsinthe frequencyrange1000-1420cm -1 havebeenreportedtobethe infraredactivenormalmodeofSO [2][3][4] groupsinthecatalysts.The bandcenteredat1115cm -1 canbeassignedtomanganesesulfates andthebroadbandin1000-1200cm -1 havealsobeenreported tocorrespondtoCe(SO 4 ) 2 formation [26] .Itisverifiedthatthereac鄄 tionsbetweenmetalsandSO 2 takeplaceunderlow鄄temperature SCRconditions.…”
Section: Table1 Physicalpropertiesofthefreshcatalystsmentioning
confidence: 99%